InLeR: A Vehicle-Mounted IoT Solution for Efficient Streetlight Monitoring - Syed Salman Alam; Najam Us Saqib; Arshad Khan; Waqas Bukhari; Riad Souissi (IEEE Access, 2025)
Maintaining compliance with light intensity standards is critical to ensuring proper illumination, particularly during nighttime, and for preserving healthy ecosystems in urban and peri-urban areas. Traditional methods, relying on manual inspections with handheld sensors, are labour-intensive and inefficient. This paper presents a novel vehicle-mounted light intensity measurement system, the “Innovative Light Evaluation Rig” (InLer), designed to significantly improve streetlight monitoring compared to conventional methods. InLer operates as an autonomous IoT device with on-edge processing, leveraging strategically placed sensors to capture light intensity in both vertical and horizontal planes. Its ability to measure light intensity at large scale continuous monitoring in three directions simultaneously within a single sampling cycle significantly enhances operational efficiency. The system features an aerodynamic and mechanically robust design, incorporating three independent lux sensors, wireless connectivity, waterproof components, and magnetic mounts for easy installation. Additionally, InLer integrates GNSS/GPS technology for precise geolocation, enabling detailed spatial analysis when combined with light-intensity data. A comprehensive calibration analysis presented in this paper validates the system’s accuracy and consistency, establishing InLer as a state-of-the-art solution with wide-ranging applications across multiple sectors.